Large-sized kidney tumor mimicking an extraorgan retroperitoneal tumor - I. A. Reva (Onkourologiâ, 2015)
The retroperitoneal space may be a site for a broad spectrum of both rare benign and malignant tumors that are in turn a focus of primary or metastatic involvement. Sarcomas, lymphomas, and different epithelial tumors (of the kidney, adrenal, and pancreas) constitute the bulk of retroperitoneal tumors. Detection of a large-sized tumor located at one of the renal poles may raise the question of whether this mass is a kidney tumor or an extraorgan retroperitoneal tumor adjacent to or growing into the kidney. In view of significant differences in treatment procedures for various retroperitoneal tumors, when the origin of the mass is unknown, there is a need for an individual approach to defining the optimal therapeutic and diagnostic tactics, by attracting specialists in allied fields.